Harvard business review on managing projects (Harvard Business School Press, 2005)
What does it take to make a project succeed? This astute collection of articles helicopters managers above the day-to-day grind of project management to understand the big-picture reasons behind why projects fly-and why they fail. Why are some bad projects so hard to kill-and why do some good projects tank? This book will help managers make decisions that enable the right projects to succeed.